Empirical potential profile model for subbands with unusual energy separation in Si(111) p-type inversion layer - Ayob, Nur Idayu; Inagaki, Takeshi J.; Daimon, Hiroshi; Takeda, Sakura Nishino (IOP Publishing, 2021)
To explain the deviation in the valence subband energy levels of the Si(111) inversion layer obtained by experiments and calculations, the band edge profile that has the same subband levels as the experimental results is searched through numerical calculations. The obtained band edge profile is characterized by its flat feature in the subsurface region over 1.2 nm from the surface of the Si substrate. By taking the second derivative of the obtained band edge profile, the carrier distribution in the space charge layer is obtained, and the existence of negative charges in the subsurface region is revealed. The origin of the negative charges is attributed to the inhomogeneous valence electron distribution due to the standing wave formation in the narrow space charge layer.